2005
DOI: 10.1053/j.nainr.2005.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Feeding Performance in Preterm Infants

Abstract: A nonexperimental study with a sample of 95 preterm infants was used to develop a model of feeding performance outcomes (proficiency, percent of prescribed volume consumed, and efficiency) using feeding readiness indicators (morbidity, maturity, behavior state at feeding start, and feeding experience). All readiness indicators were related to each other. In particular, there was a strong relationship between maturity and feeding experience. Morbidity only had an effect on efficiency; the most ill infants were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
2
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 27 publications
(13 reference statements)
2
43
2
2
Order By: Relevance
“…These studies have shown that more experience generally results in improved feeding outcomes. 16,22 The findings of this analysis supports previous findings and suggest that knowledge of feeding experience coupled with observation of early-in-the-feeding sucking behaviors could be useful for predicting success at feeding.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These studies have shown that more experience generally results in improved feeding outcomes. 16,22 The findings of this analysis supports previous findings and suggest that knowledge of feeding experience coupled with observation of early-in-the-feeding sucking behaviors could be useful for predicting success at feeding.…”
Section: Discussionsupporting
confidence: 85%
“…13,15 However, other researchers have found that more active states, including all but those associated with agitation, result in improved feeding outcomes. 16 In this study, while behavior state was moderately associated with feeding outcomes, it did not predict a clinically significant amount of the variance in those outcomes.…”
Section: Discussioncontrasting
confidence: 55%
“…There is increasing evidence that both the quantity and quality of oral feeding experience may play a role in the feeding transition. 16,20,21 Further research is required to more completely explore the effect of experience on feeding skill development. A randomized clinical trial using the significant predictors reported here, morbidity, maturity and feeding experience as factors, is recommended, with infants randomly assigned to feeding experience groups stratified by morbidity and maturity.…”
Section: Discussionmentioning
confidence: 99%
“…The scale has been used in many feeding studies. 21,26 Consistent with other studies and numerous reports suggesting that a quiet alert state is optimal for preterm infant feeding, 26 the ABSS observations were treated as interval data. Moreover, the data indicated that modeling behavior state as a linear trend alone would be problematic from a theoretical perspective, thus, both the linear and quadratic effects of behavior state were modeled.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation